1992
DOI: 10.3109/02699059209008123
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation staff stress as it relates to patient acuity and diagnosis

Abstract: Significant concern exists regarding occupational stress among nurses; the present study explored the ways in which nurses' clinical symptoms and coping styles may relate to their working on a brain injury unit or a general rehabilitation unit within an acute physical rehabilitation hospital. A comparison of rehabilitation nurses' responses with those of physical therapists within the same setting was also completed. Staff members completed questionnaires related to job stress and satisfaction, coping (Ways of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…While McLaughlin and Erdman (1992) found that psychological distress in a group of nurses working with brain injured clients was greater than for a group of physical therapists whose scores were similar to a normative sample, it was not as great as for a psychiatric outpatient norm group. Moreover, there were no significant differences between the groups in the study on ratings of job stress and job satisfaction, for which there were no normative data.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…While McLaughlin and Erdman (1992) found that psychological distress in a group of nurses working with brain injured clients was greater than for a group of physical therapists whose scores were similar to a normative sample, it was not as great as for a psychiatric outpatient norm group. Moreover, there were no significant differences between the groups in the study on ratings of job stress and job satisfaction, for which there were no normative data.…”
Section: Introductionmentioning
confidence: 82%
“…However, institutional staff providing care for people with brain injuries have traditionally been nurses who have had very little formal training in how to manage the behavior of such people. The potential importance of training in behavior management has been shown by McLaughlin and Erdman (1992) who have reported evidence which suggests that the cognitive behavioral aspects of such care contribute to higher psychological distress in nursing staff. This distress may arise partly due to lack of behavior management knowledge which results in staff-client interactions which are not conducive to optimal client rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[PT Interview] In marked contrast to staff's discomfort with client grief, observations revealed that staff were adept at handling aggression. Nurses in particular demonstrated unique proficiency with the management of aggression through such techniques as bargaining or compromising, which McLaughlin and Erdman (1992) have found typifies the interventions of nurses in brain injury rehabilitation. In the following illustrative examples, nurses utilized behavioural management techniques such as rule explanation, positive reinforcement, limit setting, task redirection, and non-threatening eye contact in order to achieve and sustain therapeutic alliance.…”
Section: Pre-interventionmentioning
confidence: 99%
“…Nevertheless, these evaluations overlooked many pre-intervention and post-intervention emotion work practices. Such oversight is critical to redress because TBI-associated injuries arguably present among the most profoundly distressing affective challenges for patients, families, and health care providers (Carroll & Coetzer, 2011;McLaughlin & Erdman, 1992). Thus, our objective was to return to the empirical data to analyze previously unexplored emotion work practices by TBI practitioners in the context of our evaluation of After the Crash.…”
Section: Introductionmentioning
confidence: 99%